LOCAL ORDINANCES - SMOKING IN THE WORKPLACE - AINSWORTH WE (Tufts Archival Research Center, 2007)
Memo from Gene Ainsworth to E A Horrigan, Jr. regarding local restrictions of workplace smoking nationwide and especially in California. Proposes two actions to be taken against workplace smoking restrictions. Discusses launching the Smoking in the Workplace Proposition as soon as possible and developing a Model Ordinance on the issue focusing on the rights of both smokers and non smokers.